Human heredity and Health (H3) in Africa kidney disease research network: a focus on methods in Sub-Saharan Africa (2015)
CKD affects an estimated 14% of adults in sub-Saharan Africa, but very little research has been done on the cause, progression, and prevention of CKD there. As part of the Human Heredity and Health in Africa (H3Africa) Consortium, the H3Africa Kidney Disease Research Network was established to study prevalent forms of kidney disease in sub-Saharan Africa and increase the capacity for genetics and genomics research. The study is performing comprehensive phenotypic characterization and analyzing environmental and genetic factors from nine clinical centers in four African countries (Ghana, Nigeria, Ethiopia, and Kenya) over a 5-year period. Approximately 4000 participants with specified kidney disease diagnoses and 4000 control participants will be enrolled in the four African countries. In addition, approximately 50 families with hereditary glomerular disease will be enrolled. The study includes both pediatric and adult participants age <1 to 74 years across a broad spectrum of kidney diseases secondary to hypertension-attributed nephropathy, diabetes, HIV infection, sickle cell disease, biopsy-proven glomerular disease, and CKD of unknown origin. Clinical and demographic data with biospecimens are collected to assess clinical, biochemical, and genetic markers of kidney disease. As of March 2015, a total of 3499 patients and controls have been recruited and 1897 had complete entry data for analysis. Slightly more than half (50.2%) of the cohort is female. Initial quality control of clinical data collection and of biosample and DNA analysis is satisfactory, demonstrating that a clinical research infrastructure can be successfully established in Africa. This study will provide clinical, biochemical, and genotypic data that will greatly increase the understanding of CKD in sub-Saharan Africa.